Impact of climate change and Coronavirus Disease (COVID-19) on inflation in Indonesia. Issue 1 (April 2021) - Wahidah, N L; Antriyandarti, E
Abstract: The novel coronavirus COVID-19 outbreak was first reported in Indonesia on March 2, 2020 and then it called for prevention. At the same time, emissions of carbon dioxide reported to have decreased that imply global climate change. Furthermore, the climate change due to a reduction in CO2 emissions during the COVID-19 pandemic affected the demand and supply side of goods and services which in turn had an impact on the economy. One of important indicators in macroeconomics is the inflation rate. Therefore, this study aims to examine the impact of climate change due to the reduction of CO2 emissions during the COVID-19 pandemic and Coronavirus disease on inflation and food inflation in Indonesia. This study uses time series daily data and analysis using Ordinary Least Squares (OLS). The result show that the number of COVID-19 cases has a negative effect on both inflation and food inflation, while the number of recovered cases has a positive effect on both dependent variables. The number of death is only significant to the inflation rate, but it is not significant to the food inflation. The variable of temperature as a proxy variable of climate change has negative influence to the food inflation, but it has not any effects to the inflation rate. In addition, the level of citizen compliance with physical distancing will determine the level of CO2 emission reduction.